Implication of p16 Promoter Methylation, the BRAFV600E Mutation, and ETS1 Expression Determination on Papillary Thyroid Carcinoma Prognosis and High-Risk Patients’ Selection - Stefana Stojanović Novković; Sonja Šelemetjev; Milena Krajnović; Ana Božović; Bojana Kožik; Uršula Prosenc Zmrzljak; Tijana Išić Denčić (Biomedicines, 2025)
Background/Objectives: Papillary thyroid carcinoma (PTC) is the most common malignancy of the endocrine system, characterized by various molecular alterations. This study evaluates the relationship between p16 promoter methylation status, BRAFV600E mutation presence, and ETS1 (E26 transformation-specific) expression, aiming to better understand their clinical significance and to enhance the risk stratification of PTC patients. Methods: p16 promoter methylation was analyzed by methylation-specific PCR (MSP), BRAFV600E by mutant allele-specific PCR amplification (MASA), ETS1 mRNA expression by quantitative PCR (qPCR), ETS1 protein expression by immunohistochemistry (IHC), and Western blot. All tested factors were further associated with the occurrence of unfavorable clinicopathological data of the patients. Results: While p16 methylation did not correlate with adverse clinical parameters or BRAFV600E mutation presence, it was significantly associated with the increased ETS1 mRNA levels. Combined p16 methylation with high ETS1 protein levels was significantly associated with advanced pT and pTNM stages. BRAFV600E-mutated PTC cases with p16 methylation showed increased mRNA and protein ETS1 expression. Conclusions: Therefore, although p16 methylation could not be used as a standalone prognostic marker, its association with elevated ETS1 levels points to its potential involvement in tumor progression and adverse clinical outcomes, particularly in BRAFV600E-mutated PTCs. Deeper insights into these interactions may enhance PTC prognosis and the selection of high-risk patients.